European college of neuropsychopharmacology network on the prevention of mental disorders and mental health promotion (ECNP PMD-MHP) - Fusar-Poli, Paolo; Meyer-Lindenberg, Andreas (European neuropsychopharmacology, 2019)
Prevention is the most promising way to reduce the high personal, familial, societal, clinical and economic costs of mental disorders in Europe and worldwide. A complementary approach is to go beyond the prevention of mental ill health, to promote good mental health. This manuscript highlights the first European consortium fostering cutting-edge multidisciplinary research in these two areas. The ECNP-funded Network on the Prevention of Mental Disorders and Mental Health Promotion (ECNP PMD-MHP) brings together European sites of excellence with different expertise for translational research collaboration, including partnerships with the industry. The ECNP PMD-MHP Network adopts a transdiagnostic, lifespan, clinical staging model which cuts across different mental disorders and different methodologies. The main aims of the ECNP PMD-MHP Network are to facilitate multidisciplinary collaboration, enhance knowledge and data sharing, standardise core assessment and outcome measures, promote clinical research, apply for grant funding, and generate research reports. By supporting collaborative research, the ECNP PMD-MHP Network will be vital for fostering European psychiatry in the field of prevention of mental disorders and promotion of good mental health.
Gesehen am 27.01.2020